The Analisis Praktik Perataan Laba Pada Perusahaan Batu Bara Ketika Krisis Energi Dan Krisis Iklim - Suyanto Suyanto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The issue of climate change was an old problem but has become a significant problem again because the situation is getting worse. In the IPCC report, the global temperature rose by 1.1˚C, and the results revealed a relationship between human activity and climate. However, in 2021, the world experienced an energy crisis in which many countries that had started using renewable energy will again use non-renewable energy to meet their energy needs. This condition will impact the companies in the energy sector, one of which is the coal sub-sector company. This study aims to analyze the effect of income tax, profitability, financial leverage and firm size on profit smoothing in coal subsector firms in 2021. This type This quantitative research uses secondary data from each company's annual reports that are processed using binary logistic regression estimation. The results of this study indicate that income tax and firm size have a significant positive effect on income smoothing. However, profitability (NPM) and financial leverage (DER) do not affect income smoothing. Other results show that the energy crisis condition is